Education and racial capitalism. Issue 3 (16th April 2022) - Gerrard, Jessica; Sriprakash, Arathi; Rudolph, Sophie
ABSTRACT: This paper works with theories of racial capitalism to show how formal education has been produced through interlocking systems of domination: capitalism, racism, and colonialism. With a focus on the enduring histories of British settler colonialism, we put forward a framework for analysing the constitutive relationship between contemporary systems of education and racial capitalism. The paper discusses three connected relations: (I) the ongoing enclosures and dispossession of land and people, with which the material infrastructures of education are built; (II) the racialised divisions of labour which education systems not only create but are also premised on, and; (III) the extraction of value in and through education, normalising hierarchised life, and steeped in racial capitalism's defining project of dehumanisation. The paper suggests that sociologies of education need to attend more fully to these relations of racial capitalism if they are to imagine beyond, and mobilise against, education's role in sustaining white supremacy.